The Effectiveness of Computer-Based Monitoring and Evaluating Vessel Inventory List for Human Resource Performance - Retno Anggoro; Fitri Suprapti; Yulius Oscar (Politeknik Ilmu Pelayaran Semarang, 2023)
The urgency of this research is how a company is able to obtain better of HR performance, develop knowledge, improve service quality and can create competitiveness for the company. This study objective is to describe whether quality knowledge can encourage technical superintendent motivation so that it can improve technical superintendent work performance during monitoring and evaluation of inventory on board using computer-based applications and knowing quality knowledge can improve technicalsuperintendent work performance so as to realize the performance of monitoring and evaluation of inventory list on board effectively. The method used in this study is the explanatory method. Data collection was carried out online from the distributed instruments. The target population in this study were employees in the fleet division at 7 (seven) shipping companies which were used as research objects with a total number of employees of 160 employees. The data obtained is then tabulated, then data reduction is carried out and after obtaining proper data, calculations are carried out using the SPSS application by carrying out validity tests, variable reliability tests, normality tests and homogeneity tests. According to the results, it is known that there is a strength relationship between the knowledge quality and human resources performance.